(untitled) (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2025)
This study investigates the effect of uphill running and ladder drill training on the 50-meter sprint speed of Grade VII students at SMPN 2 Palu. Sprinting is a fundamental motor skill that requires optimal speed, coordination, and lower limb strength, particularly during adolescence. The research employed an experimental method with a pre-test and post-test design involving 30 male students who were randomly assigned to two different training groups: one receiving uphill running training and the other undergoing ladder drill training. Both interventions were carried out over a predetermined period under the supervision of physical education instructors. Data were collected by measuring students’ 50-meter sprint times before and after the training programs. The paired sample t-test was used to analyze the differences between pre- and post-test results within each group. The findings revealed that both training methods significantly enhanced sprint performance. The uphill running group achieved a t-value of 17.580, while the ladder drill group recorded a t-value of 15.572, with both results indicating a significance level of p < 0.05. These results suggest that uphill running, which emphasizes power and stride mechanics, and ladder drills, which enhance agility and foot coordination, are both effective in improving short-distance sprint speed. The study concludes that incorporating either of these training modalities into physical education curricula can effectively enhance the sprinting capabilities of junior high school students. Future research may explore the combined effects of both training types or their impact on other motor abilities.